2017
DOI: 10.5194/adgeo-44-67-2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of damaging hydrogeological events on people throughout 15 years in a Mediterranean region

Abstract: Abstract. Damaging Hydrogeological Events (DHE) are defined as rainy periods during which landslides and floods can damage people. The paper investigated the effects of DHE on people living in Calabria (southern Italy) in the period 2000-2014, using data coming from the systematic survey of regional newspapers. Data about "fatalities", people "injured" and people "involved" (not killed neither hurt) were stored in the database named PEOPLE, made of three sections: (1) event identification, (2) victim-event int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 20 publications
3
22
0
Order By: Relevance
“…In an Australian study by Franklin et al (2014), 10% (n=13) of participants responded that they had swum in floodwater; however, it is unclear if this behaviour was exercised for recreational reasons. Aceto et al (2017) report that fishing and other recreational activities are responsible for one fatality (5%) during damaging hydrogeological events in the Italian Calabria Region between 2000 and 2014. Furthermore, 22 out of 154 injuries related to these events can be related to fishing and recreational activities as well as 36 (2%) to general involvements in the events.…”
Section: Activities and Risk-taking Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…In an Australian study by Franklin et al (2014), 10% (n=13) of participants responded that they had swum in floodwater; however, it is unclear if this behaviour was exercised for recreational reasons. Aceto et al (2017) report that fishing and other recreational activities are responsible for one fatality (5%) during damaging hydrogeological events in the Italian Calabria Region between 2000 and 2014. Furthermore, 22 out of 154 injuries related to these events can be related to fishing and recreational activities as well as 36 (2%) to general involvements in the events.…”
Section: Activities and Risk-taking Behavioursmentioning
confidence: 99%
“…A total of four people died while trying to rescue another person with two people injured during damaging hydrogeological events in the Italian Calabria region (Aceto et al, 2017). Ashley and Ashley (2008) Krishna et al (2018) in Tamil Nadu, India, found that children were commonly used to transport information between neighbours in small villages despite being perceived to be at higher risk during natural disasters.…”
Section: Loss Reduction Knowledge and Warningsmentioning
confidence: 99%
“…The limitations associated with documentary sources are widely addressed in literature [21,32,33]. The most important ones are as follows:…”
Section: Euff Databasementioning
confidence: 99%
“…Narratives of fatal events gathered from documentary sources were disaggregated in database fields describing victim's profile and the circumstances of the deaths. EUFF follows the data organization already tested in published papers [18,21,23,34]. Each row contains data about a single fatality, organized in fields clustered in six sections, the detailed description of which is available in [18] (2019).…”
mentioning
confidence: 99%
“…In addition to flood fatalities, those due to landslides, lightning, windstorms, hail, or storm surges in the Calabria Region (southern Italy) were analysed for the 2000-2014 period by Aceto et al [29] and for the 2000-2016 period by Petrucci et al [30]. Badoux et al [31] investigated fatalities related to several natural hazards in Switzerland for the 1946-2015 period.…”
Section: Introductionmentioning
confidence: 99%